Performance of wood impregnated with alkoxysilanes - Canosa, Guadalupe (2016)
The wood, very heterogeneous and complex material, changes its volume by water absorption ordesorption causing swelling or shrinkage and also it can be degraded both by action ofmicroorganisms and fire; the above-mentioned is a great inconvenient for most commercial uses.Solid wood specimens of Araucaria angustifolia were impregnated with alkoxysilanes hydrolyzed andcondensed ?in situ? by the sol-gel process. Alkoxysilanes selected were aminopropylmethyldiethoxysilane and aminopropyl triethoxysilane; it was also used the aminopropylmethyldiethoxysilane/aminopropil triethoxysilane mixture in 50/50 w/w ratio. The pH was adjusted toalkaline value for controlling kinetic of hydrolysis and condensation reactions.Impregnation process was carried out at 45?50 ºC in an autoclave, controlling the operating conditionsfor achieving different weight gains.Unmodified and modified wood specimens were exposed to brown rot (Polyporus meliae) and whiterot (Coriolus versicolor) under laboratory conditions.The results indicate that the improved resistance to fungal exposure would be based on the woodchemical modification (the protection of cellulose caused by steric hindrance of ≡Si-O-Cellulosepreventing the formation of enzyme-substrate complex). Moreover, the results also would be based onthe enhanced dimensional stability of the treated wood; the quoted high dimensional stability, whichlimits the growth of the spores, is supported in the hydrophobicity generated by both the decreasing ofthe amount of polar hydroxyl groups and the partial occupation of pores with polysiloxanes.Fire laboratory tests were carried out in Two-Foot Tunnel (flame spread index, panel consumption andsmoke density) and in TGA detector (mass loss).The performance can be explained according the reactivity of the alkoxides; the results indicate that asweight gain increase the performance of impregnants against fire also does.